Building family practice skills: methods, strategies, and tools - Mark Ragg D (Belmont, CA : Thomson Brooks/Cole, 2006)
This book presents a transtheoretical 'response system framework' for understanding family practice. This framework organizes theoretical information, assessment protocols, skills, and intervention strategies into a learning structure that helps students understand myriad client situations and the intervention strategies that would be most appropriate for those specific situations. Using this over-arching structure, and focusing on two systems of response--action systems (how family members behave and interrelate) and processing systems (how family members interpret/feel) - [the author] guides readers through the five parts of the book with the goal of building holistic family intervention skills.
Keywords: Family Social Work; Family Counseling; Social Work; Social Sciences